Hospital Incident Reporting Behaviour in Indonesia - Luxandre Agung; Kemala Rita Wahidi; Hasyim (Jurnal Cinta Nusantara (JCN), 2023)
Patient safety is of the main concern in global healthcare. To promote better patient safety, incident reporting is encourage for future betterment. As the largest constituent in numbers of hospital healthcare professionals, nurses have major contribution in implementing patient safety. Nursing career ladder is implemented as an effort to advance nurses’ professionalism in providing safer, more effective and efficient care, also to ensure work satisfaction, career and professional advancement in Indonesia. This research aims to analyze the effect of nurse career ladder and implementation of patient safety goals on incident reporting behavior at inpatient nurses of Hospital X. Survey was conducted by distributing questionnaires to 82 nurses. The results show that career ladder level with patient safety goals implementation have a significant positive effect on incident reporting behavior. Career ladder has a positive effect on patient safety goals implementation. Patient safety goals implementation has a positive effect on incident reporting behavior. Career ladder level has no significant effect on incident reporting behavior. The managerial implications, hospital are encouraged to ensure that assessments of nurse career ladder level advancement are followed by not only increasing level of competency, but also increasing consistency to implement patient safety goals and incident reporting behavior.